2020
DOI: 10.3390/cancers12041053
|View full text |Cite
|
Sign up to set email alerts
|

Self-Collection for Cervical Screening Programs: From Research to Reality

Abstract: In 2018, there were an estimated 570,000 new cases of cervical cancer globally, with most of them occurring in women who either had no access to cervical screening, or had not participated in screening in regions where programs are available. Where programs are in place, a major barrier for women across many cultures has been the requirement to undergo a speculum examination. With the emergence of HPV-based primary screening, the option of self-collection (where the woman takes the sample from the vagina herse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…In 2018, there were an estimated 570,000 new cases of cervical cancer on a global scale, most of them occurring with women who either had no access to cervical screening, or had not participated in screening in regions where the program is available. [ 13 ] Evidence-based medical surveys show that screening is an effective means for the prevention and treatment of cervical cancer. [ 14 ] Early diagnoses and standardized treatments of cervical cancer and its precancerous lesions can effectively reduce the incidence and mortality of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, there were an estimated 570,000 new cases of cervical cancer on a global scale, most of them occurring with women who either had no access to cervical screening, or had not participated in screening in regions where the program is available. [ 13 ] Evidence-based medical surveys show that screening is an effective means for the prevention and treatment of cervical cancer. [ 14 ] Early diagnoses and standardized treatments of cervical cancer and its precancerous lesions can effectively reduce the incidence and mortality of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Few device or assay combinations are designed for medium-to-high throughput testing, meaning that their processing is more labour-intensive and time-consuming than is the processing of clinician-taken samples. 52 Thus, even in programmes that have already switched to HPV testing, a large-scale roll-out of self-sampling would require infrastructure that most programmes do not have readily available. Additionally, triage is required for women who are HPV-positive, and, at present, there are no clinically validated molecular biomarkers that could expedite triage on a self-sample.…”
Section: Optimising Responsesmentioning
confidence: 99%
“…These caveats suggest that self-sampling might not be a realistic strategy to rapidly scale up during this pandemic; however, it is certainly a promising option for the future. 52 …”
Section: Optimising Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPV testing in self-sampled cervical exfoliates has been shown to increase the participation of women in oncological screenings particularly in never- or under-screened populations. Hawkes et al, in their review, discussed several studies that have examined the self-collection of cervical samples for HPV-based cervical screening including the collection devices and assays [ 26 ]. The authors concluded that self-collection will be crucial for global screening programs and the elimination of cervical cancer as a public health problem.…”
mentioning
confidence: 99%